Pendidikan dan Etatisme Negara - Isfridus Tafin, Isfridus Tafin (JURNAL PROPHETA, 2021)
Education is one of the human rights that essentially belong to people in the world.As far as it is concerned, the good education aims to develop human resources that is usedfor human competition in the era of globalization. Furthermore, education forms any kindof human dignity of human’s life. Throughout education, it is the obligation for humanbeing to survive, to learn, to collaborate any of the experiences and knowledge in order toadapt themselves in the modern society. To maintain the aim of education, one thing thatshould be concerned is to achieve any changes of human’s ways of life in the society.This kind of changes brought a great inter-relation (mutual symbioses) between thehuman being and the society.It is the benefit for all the citizens upon the right of education to achieve a greatprosperity in the society. Hence, the national education is determined as the concreteeffort from the government in order to fulfill its obligation in the form of a goodeducation that offered to all the citizens in the country. As far as it is concerned, the moreeducation program is to be achieved, the more the country is to be loved by its citizens forthe benefits of their prosperity in the society.However, the goal of the education system need to be revised by the governmentregarding to the nation astaticism obstacles due to the variety of nation problems, that is,political system, social economic, covid-19 pandemic.